Tuna Massage Training as An Effort to Improve the Nutritional Status of Toddlers - Sumarni Sumarni; Fitria Prabandari (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Difficulty eating in children cause malnutrition, dehydration, underweight, electrolyte imbalance, impaired cognitive development, anxiety disorders, and in more severe cases can be a life-threatening condition. Tuina massage is a massage technique that can overcome eating difficulties in toddlers. The purpose of this activity is to increase the knowledge and skills of health cadres about nutritional health and Tuina massage. The service was carried out in Pasir Lor village, Karanglewas district, which was attended by 23 cadres. Data collection techniques were carried out using questionnaires about toddler nutrition and observation sheets to assess Tuina's massage skills. The results of the activity showed that the knowledge of cadres before training was mostly in the sufficient category, while the knowledge of cadres after attending the training showed that the level of knowledge of cadres was mostly in the good category. Most of the health cadres have good skills in doing Tuina massage. The training activities were effective and able to increase the knowledge and skills of cadres about toddler nutrition and developmental problems and Tuina massage.